2015
DOI: 10.1097/pec.0000000000000350
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Neonatal Transport Scoring Systems and Transport-Related Mortality Score for Predicting Neonatal Mortality Risk

Abstract: The TREMS scoring system is a simple scoring system with a high specificity for predicting mortality. Further studies with larger sample size including more centers and newborn infants with diverse clinical problems are needed to assess the validity and reliability of the TREMS scoring system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
1
5
0
2
Order By: Relevance
“…Gestational age affects significantly some of the transport performance measures in the effectiveness domain: stabilisation time and unintended hypothermia [1,3,13,27,32]. In the present study, unnoticed hypothermia was outstandingly more frequent than reported in other studies [37] and similar to others [42], and prevalent in preterm and term babies, but significantly descended in the second period probably reflecting a better performance. Besides, the adequate definition for systemic arterial hypotension in newborns is yet to be established, but it is clear that gestational age needs to be taken into account [47].…”
Section: Discussionsupporting
confidence: 74%
“…Gestational age affects significantly some of the transport performance measures in the effectiveness domain: stabilisation time and unintended hypothermia [1,3,13,27,32]. In the present study, unnoticed hypothermia was outstandingly more frequent than reported in other studies [37] and similar to others [42], and prevalent in preterm and term babies, but significantly descended in the second period probably reflecting a better performance. Besides, the adequate definition for systemic arterial hypotension in newborns is yet to be established, but it is clear that gestational age needs to be taken into account [47].…”
Section: Discussionsupporting
confidence: 74%
“…) 15 [11][12][13][14][15][16][17][18] баллов. Шкала применялась в авторской версии, без модификаций.…”
Section: оценка по шкале Ntiss на момент осмотра реаниматолога транспортной бригады составила (медиана [Iqr]unclassified
“…AUC для прогнозирования летального исхода при использовании шкал MINT составила 0,92, для шкал SNAP-PE-II и TREMS -0,84. Чувствительность, специфичность, положительная предиктивная ценность и отрицательная предиктивная ценность составила 96%, 54%, 31% и 98% -для MINT, 87%, 70%, 39%, 96%для SNAP-PE-II и 82%, 71%, 38%, 94% -для TREMS [15]. Шкалы также схожи по возможности прогнозирования летального исхода со шкалой NTISS, однако полученный нами уровень положительной предиктивной ценности оказывается неприемлемо низким.…”
Section: дискуссияunclassified
“…On admission, detailed clinical assessment of each baby was carried out and the following parameters documented; the rectal temperature, random plasma glucose, respiratory rate, heart rate, oxygen saturation, blood pressure and serum bicarbonate. The Transport Risk Index of Physiologic Stability (TRIPS) score was calculated for each of the neonates and classified as low (0-10), moderate (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), severe (21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and very severe (>30) [16][17][18][19].…”
Section: Thismentioning
confidence: 99%
“…The TRIPS score has been used as a tool to evaluate the effect of transport on illness severity in newborns even in some developing countries [12]. The TRIPS score is not being used in Nigeria and many other developing countries however, it would be a useful tool in such settings as it would allow health care workers assess the impact of transport practices on outcomes of these sick newborns and make necessary adjustments.…”
mentioning
confidence: 99%